Razvoj slovenske paremiologije in paremiološke terminologije - Ulčnik, Natalija (Slavia Centralis, 2020)
DEVELOPMENT OF THE SLOVENE PAREMIOLOGY AND PAREMIOLOGICAL TERMINOLOGYThe article focuses on terminology referred to paremiology – a science which examines proverbs and related units. It outlines the question of paremiology’s scientifc autonomy and the problem of defning the basic units of the study, i. e. paremia. In the conclusion the analysis emphasizes a need for new paremiological linguistic researches that will also help to expand terminology.
Keywords: paremiology; paremia; proverbial units; terminology